New Onset Left Bundle Branch Block and Its Short Term Outcomes - Salahud Din, Muhammad; Hayat, Yasir; Shah, Rayan (Indus Journal of Bioscience Research, 2025)
Background: Recognition of ischemia is often complicated when patients present with a new-onset left bundle branch block (LBBB), which may also serve as an early indicator of clinical deterioration. However, the short-term prognosis of such presentations in general hospital populations is still insufficiently characterized. Objective: To evaluate 30-day adverse clinical outcomes and identify practical prognostic markers among adults diagnosed with new-onset LBBB. Methods: A prospective descriptive cohort study was conducted at the MTI-HMC tertiary cardiology facility in Peshawar over a six-month period. Adults aged 18–80 years with newly diagnosed LBBB on 12-lead ECG were consecutively recruited. Prespecified 30-day outcomes included all-cause mortality, cardiogenic shock, and major adverse cardiovascular events (MACE), comprising myocardial infarction, heart failure-related hospitalizations, sustained arrhythmias, urgent revascularizations, and stroke/transient ischemic attacks (TIA) as well as all-cause readmission. Baseline parameters included ECG (QRS duration/morphology), left ventricular ejection fraction (LVEF) via echocardiography, and high-sensitivity troponin. Data were analyzed using descriptive statistics and post-stratification chi-square tests (α = 0.05, two-sided). Results: Of the 223 participants (mean age 58.8 ± 10.9 years; 74.9% male), average QRS duration was 138.8 ± 14.2 ms, with 43.9% exhibiting QRS >140 ms. Mean LVEF was 41.6 ± 10.8%, and 43.0% had LVEF <40%. High-sensitivity troponin was elevated in 39.9% of cases. Within 30 days, MACE occurred in 19.7% of participants, including heart failure admissions (8.5%), myocardial infarction (6.7%), sustained arrhythmias (4.9%), urgent revascularizations (3.6%), and no strokes/TIA. Mortality reached 8.1%, cardiogenic shock 5.4%, and overall readmission 15.7%. Subgroup analyses revealed no statistically significant differences in MACE based on age, diabetes, hypertension, QRS category (≤140 vs >140 ms), or LVEF classification (≥40% vs <40%) (p ≥ 0.366). However, higher rates of shock (8.2% vs 3.2%) were noted with QRS >140 ms, and greater mortality (11.5% vs 5.5%) was observed in those with LVEF <40%. Conclusions: New-onset LBBB is linked to significant 30-day adverse outcomes in real-world clinical settings. Easily obtainable bedside indicators—such as pronounced QRS prolongation and reduced LVEF—may assist in prioritizing early intervention. Strategies incorporating ECG interpretation, high-sensitivity troponin assessment, early echocardiography, structured discharge planning, and standardized follow-up at 30 days are recommended. Validation through multicenter studies is essential.